Assessment of elderly fragility in outpatient chemotherapy treatment - Josiane Caroline Zimmermann; Margrid Beuter; Jamile Lais Bruinsma; Ana Cristina Geiss Casarolli; Caren da Silva Jacobi; Larissa Venturini (Universidade Federal de Santa Maria, 2017)
Aim: to characterize and verify the fragility of the elderly in outpatient chemotherapy treatment in a university hospital of southern Brazil, and to identify the association between fragility and the following variables: chemotherapeutic effect, treatment time and selfreported diseases. Method: cross-sectional study conducted with 70 elderly in the chemotherapy outpatient, from August to September 2014 by means of Edmonton Frail Scale and characterization form. Results: fifty percent did not present fragility, 31.4% were apparently vulnerable and 18.6% had some level of fragility. Among the frail elderly, 15.7% had mild fragility, 1.4% moderate and 1.4% severe. The association between frailty and self-reported diseases, time of treatment and chemotherapeutic effects was not statistically significant. Conclusion: it was point to applicability of the scale to identify predisposing factors for the fragility syndrome and to enable preventive actions for the elderly in chemotherapeutic treatment